Preparation method of porous structure precursor and hole structure positive electrode material

Through the simplified preparation method of porous structure precursor, the process complexity of the positive electrode material is solved, and the hole structure positive electrode material is formed, which improves the circulation and rate performance of lithium-ion batteries and enhances the stability of the material.

CN119320177APending Publication Date: 2025-01-17JINGHE NEW TOWN SHAANXI COAL TECH RES INST NEW ENERGY MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411469658.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing method for preparing the positive electrode precursor is complex in process and difficult to operate, resulting in the collapse of the layered structure of the ternary positive electrode material during the cycle charging and discharge process, and the inability to effectively release the internal stress of the material, limiting the cycling and rate performance of the battery.

Method used

Using the preparation method of porous structure precursor, a co-precipitation reaction is carried out by preparing metal salt solution, sodium hydroxide solution and sodium carbonate solution to form a composite precipitation agent and a single precipitation agent, controlling the reaction conditions and washing process, and preparing a porous structure The precursor is mixed with lithium salt and sintered at high temperature to form a hole structure positive electrode material.

Benefits of technology

The precursor preparation process is simplified, the complete hole structure formation of the positive electrode material is achieved, the contact area between the electrolyte and the material is increased, the Li+ transmission path is shortened, the circulation and rate performance of the material is improved, and the structural stability is enhanced. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320177A_ABST
    Figure CN119320177A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a porous structure precursor. The preparation method comprises the following steps: preparing a metal salt solution, a sodium hydroxide solution, ammonia water and a sodium carbonate solution; preparing a base solution in a reaction kettle by utilizing a sodium hydroxide solution, ammonia water and a sodium carbonate solution; enabling a metal salt solution and a sodium hydroxide solution to flow into a reaction kettle in parallel to be subjected to a coprecipitation reaction with the base solution, and after nucleation is stable, enabling ammonia water to flow into the reaction kettle for continuous reaction; after the granularity of the materials in the reaction kettle reaches the qualified granularity, stopping the reaction, and discharging; washing the material by using an alkali solution and water in sequence, and then dehydrating, drying and demagnetizing to obtain a precursor; the invention also discloses a preparation method of the positive electrode material with the hole structure, which comprises the following steps: mixing the porous structure precursor with a lithium salt, and sintering at high temperature to obtain the positive electrode material with the hole structure. The method provided by the invention solves the problems of complex process and high operation difficulty of the existing positive electrode precursor preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery materials and relates to a method for preparing a porous structure precursor. The present invention also relates to a method for preparing a hole structure positive electrode material. Background Art

[0002] The positive electrode material is an important component of lithium-ion batteries and is related to the overall capacity, cycle, rate, safety and other performance of the battery. The ternary positive electrode material has the characteristics of high capacity, but as the cycle charge and discharge proceeds, the layered structure of the ternary positive electrode material will collapse, resulting in the inability to release the internal stress of the material, which seriously restricts the battery's cycle performance, rate performance, etc.

[0003] At present, the optimization of the above problems is mainly to dope certain special elements in the ternary precursor to improve the stability of the material, and on the other hand, to optimize the structural design of the positive electrode material. Studies have shown that special configurations such as hollow and concentration gradient positive electrode materials have good optimization effects on battery cycle performance, rate performance, etc., such as the preparation method of a porous structure precursor disclosed in a Chinese patent with a publication date of July 22, 2022 and a publication number of CN114772556B. In the preparation process of the precursor, a carbonate system precipitant is used for the growth of the inner core stage to form a carbonate precipitate, and a sodium hydroxide solution is used as a precipitant in the outer shell growth stage to form a hydroxide precipitate. The overall structure is a carbonate precipitate inner core + a hydroxide outer shell, and a hollow positive electrode material is formed during the lithium-doped high-temperature sintering process. A Chinese patent with a publication date of April 12, 2019 and a publication number of CN109616664A discloses a method for preparing a ternary material, using organic polymer particles as pore-forming agents and the carbonized material in lithium sintering as a reducing agent to prepare a high-nickel ternary positive electrode material with internal voids in the secondary particles and a transition metal ion gradient layer in the primary particles. A Chinese patent with a publication date of March 27, 2020 and a publication number of CN110921723A discloses a method for preparing a hollow positive electrode precursor. The synthesis process is divided into two stages, ensuring that the stirring linear speed of the second stage is greater than the linear speed of the first stage, and the flow rate of the salt solution in the second stage is less than that of the first stage, forming an internally hollow and externally solid precursor, controlling the degree of hollowness and solidity, and producing a hollow precursor.

[0004] The above methods all require the addition of organic matter, nucleating agents or replacement of precipitants during the preparation of hollow positive electrode materials, and the process operations are relatively cumbersome and complicated. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a porous structure precursor, which solves the problems of complex process and difficult operation of the existing positive electrode precursor preparation method.

[0006] Another object of the present invention is to provide a method for preparing a positive electrode material with a hole structure based on the above precursor.

[0007] The technical solution adopted by the present invention is a method for preparing a porous structure precursor, which is specifically implemented according to the following steps: Step 1, preparing a metal salt solution, a sodium hydroxide solution, an ammonia solution and a sodium carbonate solution; Step 2, preparing a base liquid in a reaction kettle using the sodium hydroxide solution, ammonia water and sodium carbonate solution prepared in step 1; Step 3, the metal salt solution and the sodium hydroxide solution are simultaneously flowed into the reactor to undergo a co-precipitation reaction with the bottom liquid, and after the nucleation is stable, ammonia water is flowed into the reactor to continue the reaction; Step 4, after the particle size of the material in the reactor reaches the qualified particle size, stop the reaction and discharge the material; Step 5, washing the material obtained in step 4 with an alkaline solution and water in turn, and then dehydrating, drying and demagnetizing to obtain a precursor.

[0008] The present invention is also characterized in that: In step 1, the concentration of the sodium hydroxide solution is 2.5% to 32.5%, the concentration of the ammonia water is 2.5% to 32.5%, and the concentration of the sodium carbonate solution is 2.5% to 35%.

[0009] In step 1, the metal salt solution is a mixed solution of nickel salt, cobalt salt and manganese salt, wherein the nickel salt is any one of nickel sulfate, nickel fluoride and nickel nitrate; the cobalt salt is any one of cobalt sulfate, cobalt fluoride and cobalt nitrate; the manganese salt is any one of manganese sulfate, manganese fluoride and manganese nitrate; the molar amount of nickel, cobalt and manganese atoms accounts for the total molar amount of nickel, cobalt and manganese atoms, respectively, the ratio is x, y and z, wherein 0.6≤x<1.0, 0<y<0.4, 0<y<0.4, x+y+z=1; the total metal ion concentration in the metal salt solution is 1.5mol / L~2.5mol / L.

[0010] In step 2, the base liquid is prepared at 50°C-80°C, the pH value of the base liquid is 10.5-13.0, and the mass ratio of sodium hydroxide to sodium carbonate in the base liquid is 1:0.6-1.

[0011] During the entire reaction process of step 3, the pH of the reaction solution is controlled at 10.5-13.0, the ammonia concentration is controlled at 0.05 mol / L-0.2 mol / L, the stirring linear velocity is 5.0 m / s-9.0 m / s, the temperature range is 50°C-80°C, the flow rate of the metal salt solution is 1.5 L / h-5 L / h, the flow rate of the sodium hydroxide solution is 0.6 L / h-3 L / h, and the flow rate of the ammonia water is 0.1 L / h-1 L / h.

[0012] In step 4, the standard of qualified particle size is 2μm<D50<10μm, 0.5<diameter distance<1.0, and the particle size distribution conforms to the normal distribution.

[0013] In step 5, the alkaline solution is a NaOH solution with a concentration of 0.05 mol / L to 3 mol / L. The ratio of the mass of the material to the volume of the alkaline solution and water during the washing process is material: alkali: water = 1 kg: 5 to 15 L: 5 to 15 L. The washing time is 0.5 h to 2 h.

[0014] Another technical solution adopted by the present invention is a method for preparing a hole structure positive electrode material, which is specifically implemented according to the following steps: the above-mentioned porous structure precursor is mixed with a lithium salt and then sintered at a high temperature to obtain a hole structure positive electrode material.

[0015] Another technical solution of the present invention is also characterized in that: The lithium salt is one of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate. The ratio of the amount of total metal ions in the precursor to the amount of lithium atoms in the lithium salt is 1:1-1.05. The sintering temperature is 600°C~1000°C and the sintering time is 10h~20h.

[0016] The beneficial effects of the present invention are: (1) In the process of preparing the precursor, the method of the present invention uses a composite precipitant in the first stage and a single precipitant in the second stage. During the process, there is no need to add other reagents, switch complexing agents, frequently change process conditions or modify production equipment. Only ammonia water needs to be introduced after the nucleation is stable to directly prepare the porous structure precursor. The operation is simple and practical. (2) The method of the present invention achieves the purpose of controlling the size of the positive electrode material pores by controlling the alkali content, carbonate content and metal salt flow rate in the base liquid. Increasing the alkali content makes the internal grains of the porous precursor finer and easier to melt during the sintering process; increasing the carbonate content makes the precursor have fewer flocculent small grains in the pores during the sintering process; increasing the salt flow rate increases the porous structure of the precursor; the combination of the three makes the final positive electrode material pore size controllable at 0.5~5.0μm; (3) The mass ratio of sodium hydroxide to sodium carbonate in the bottom liquid precipitant of the method of the present invention is 1:0.6-1.0. If the sodium carbonate content is too little, the sintering process cannot ensure that a complete hole structure is formed inside the precursor due to the presence of less carbonate ions; if the sodium carbonate content is too much, more fine grains will be generated inside the precursor. During the sintering process, the fine grains will be melted and bonded together, resulting in the inability to form a complete hole structure; (4) The positive electrode material prepared by the method of the present invention has a complete hole structure, and there are no flocculent small crystals in the hole. After it is made into a lithium-ion battery, sufficient electrolyte enters the hole structure, which increases the contact area between the electrolyte and the positive electrode material and increases the Li +transmission channel, and greatly shortens the Li + The transmission pathway is improved, and the hole structure increases the release of stress during the cyclic charge and discharge process of the positive electrode material. The dense shell improves the stability of the material structure, and comprehensively improves the cycle performance and rate performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a flow chart of the method for preparing a porous structure precursor of the present invention; Figure 2 is a cross-sectional electron microscope photograph of the porous structure precursor prepared in Example 1 of the present invention; Figure 3 This is a cross-sectional electron microscope photograph of the hole structure positive electrode material prepared in Example 1 of the present invention; Figure 4 is a cross-sectional electron microscope photograph of the precursor prepared in Comparative Example 1 of the present invention; Figure 5 This is a cross-sectional electron microscope photograph of the positive electrode material prepared in Comparative Example 1 of the present invention; Figure 6 is a cross-sectional electron microscope photograph of the precursor prepared in Comparative Example 2 of the present invention; Figure 7 is a cross-sectional electron microscope photograph of the positive electrode material prepared in Comparative Example 2 of the present invention; Figure 8 It is a comparison chart of the capacity retention rate of the positive electrode materials prepared in Example 1 of the present invention and Comparative Example 1 at different rates; Fig. 9 It is a comparison chart of the capacity retention rate of the positive electrode materials prepared in Example 1 of the present invention and in Comparative Example 1 after 50 cycles of charging. DETAILED DESCRIPTION

[0018] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0019] The preparation method of the porous structure precursor of the present invention is as follows: Figure 1 As shown, the specific implementation steps are as follows: Step 1, prepare the solution: Add metal salt crystals into deionized water at a temperature of 40°C and stir until completely dissolved to obtain a metal salt solution with a total metal ion concentration of 1.5 mol / L to 2.5 mol / L; prepare a sodium hydroxide solution with a concentration of 2.5% to 32.5%, an ammonia solution with a concentration of 2.5% to 32.5%, and a sodium carbonate solution with a concentration of 2.5% to 35%.

[0020] The metal salt crystals are mixed crystals of nickel salt, cobalt salt and manganese salt, wherein the nickel salt is any one of nickel sulfate, nickel fluoride and nickel nitrate; the cobalt salt is any one of cobalt sulfate, cobalt fluoride and cobalt nitrate; the manganese salt is any one of manganese sulfate, manganese fluoride and manganese nitrate. The ratios of the molar amount of nickel, cobalt and manganese atoms to the total molar amount of nickel, cobalt and manganese atoms are x, y and z respectively, wherein 0.6≤x<1.0, 0<y<0.4, 0<y<0.4, x+y+z=1.

[0021] Step 2, prepare the base solution: Add deionized water to the reactor, heat to a temperature of 50°C to 80°C, start stirring the reactor, control the stirring linear speed to 5.0m / s to 9.0m / s, then add sodium hydroxide solution, ammonia water and sodium carbonate solution to form a reactor bottom liquid with a pH of 10.5 to 13.0, and the mass ratio of sodium hydroxide to sodium carbonate in the bottom liquid is 1:0.6-1.

[0022] Step 3, start the reaction. The reaction is divided into two stages: nucleation and growth. The composite precipitant formed by sodium hydroxide and sodium carbonate is used as the first-stage precipitant, and the single precipitant of sodium hydroxide is used as the second-stage precipitant. Specifically, the metal salt solution and the sodium hydroxide solution are flowed into the reactor to undergo a co-precipitation reaction with the bottom liquid. After the nucleation is stable, ammonia water is flowed into the reactor to continue the reaction. During the reaction process, when the liquid level of the reaction liquid rises to the upper limit level, the clearing pump is turned on to keep the liquid level of the reactor constant.

[0023] During the entire reaction process, the pH of the reaction liquid is controlled at 10.5~13.0, the ammonia concentration is controlled at 0.05mol / L~0.2mol / L, the stirring linear speed is 5.0m / s~9.0m / s, the temperature range is 50℃~80℃, the flow rate of the metal salt solution is 1.5L / h~5L / h, the flow rate of the sodium hydroxide solution is 0.6L / h~3L / h, and the flow rate of the ammonia water is 0.1L / h~1L / h.

[0024] Step 4, after the particle size of the material in the reactor reaches the qualified particle size, the reaction and the clearing are stopped, and the material is discharged. Among them, the standard of the qualified particle size is 2μm<D50<10μm, 0.5<diameter distance<1.0, and the particle size distribution conforms to the normal distribution.

[0025] Step 5, washing the material obtained in step 4 with alkaline solution and water in turn, and then dehydrating, drying and demagnetizing to obtain a precursor, the core of which is a mixture of extremely loose carbonate precipitates and hydroxide precipitates, and the outer shell is a dense hydroxide precipitate.

[0026] The alkaline solution used is NaOH solution with a concentration of 0.05mol / L~3mol / L. The ratio of the mass of the material to the volume of the alkaline solution and water during the washing process is material: alkali: water = 1kg: 5~15L: 5~15L. The washing time is 0.5h~2h.

[0027] The method for preparing the hole structure positive electrode material of the present invention is specifically implemented according to the following steps: The precursor obtained in the above step 5 is mixed with a lithium salt and then sintered at high temperature to obtain a hole structure positive electrode material. The lithium salt is one of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate, the ratio of the amount of total metal ions in the precursor to the amount of lithium atoms in the lithium salt is 1:1-1.05, the sintering temperature is 600°C~1000°C, and the sintering time is 10h~20h.

[0028] In this step, the lithium salt is dehydrated at high temperature, and the loose inner core interface of the precursor migrates to the outer shell to form a hollow structure oxide with a diameter of 2μm~10μm and a hollow structure diameter of 0.5μm~5μm.

[0029] Example 1 The preparation method of the porous structure precursor in this embodiment is: Step 1, preparing a solution: weigh nickel sulfate, cobalt sulfate, and manganese sulfate crystals according to a molar ratio of 80:10:10, and stir and mix with 40°C deionized water until completely dissolved to obtain a metal salt solution with a total metal ion concentration of 2 mol / L, and prepare a 5% sodium hydroxide solution, a 14% ammonia solution, and an 8% sodium carbonate solution.

[0030] Step 2, preparing the bottom liquid: adding deionized water to the reactor, heating to a temperature of 60°C, starting the reactor to stir, and then adding sodium hydroxide solution, ammonia water and sodium carbonate solution to form the reactor bottom liquid, controlling the bottom liquid pH to 12.0, the ammonia concentration to 0.05 mol / L, the reactor stirring linear speed to 7 m / s, and the mass ratio of sodium hydroxide to sodium carbonate in the bottom liquid to 1:0.7.

[0031] Step 3, open the kettle and let the metal salt solution and sodium hydroxide solution flow to the reactor to react with the bottom liquid for coprecipitation, control the flow rate of the metal salt solution to 2L / h, the flow rate of the sodium hydroxide solution to 0.8L / h, and after the nucleation is stable, open the ammonia valve in the growth stage and flow into the reactor, control the flow rate of the metal salt solution to 2L / h, the flow rate of the sodium hydroxide solution to 0.8L / h, and the flow rate of the ammonia to 0.15L / h, and control the pH to 11.8±0.02, the ammonia concentration to 0.2mol / L±0.01mol / L, the temperature to 68°C, and the stirring linear speed to 7m / s during the reaction. During the reaction, when the liquid level of the reaction liquid rises to the upper limit liquid level, turn on the clearing pump to keep the liquid level of the reactor constant.

[0032] Step 4: After the D50 of the material in the reactor is 3.0 μm, stop the reaction and clear out, and discharge the material.

[0033] Step 5: Wash the material in step 4 with a sodium hydroxide solution having a concentration of 2 mol / L for 1 hour, dehydrate it and then wash it with pure water for 1 hour. After dehydration, send it to the drying section, and after drying, send it to the demagnetization and packaging section for treatment to obtain the target precursor.

[0034] The prepared precursor was analyzed by electron microscopy, and the results are as follows: Figure 2 As shown, it can be seen that the precursor has an obvious core + shell structure, and the core is porous.

[0035] The preparation method of the hole structure positive electrode material is: The precursor prepared in the above step 5 is mixed with lithium hydroxide in a ratio of total metal ion mole to lithium atomic mole of 1:1.05, and sintered at 850° C. in an oxygen atmosphere for 10 hours to obtain a hole structure positive electrode material.

[0036] The cross-section electron microscope photo analysis of the obtained positive electrode material showed the following results: Figure 3 As shown, it can be seen that there is an obvious void structure inside the material.

[0037] Example 2 The preparation method of the porous structure precursor in this embodiment is: Step 1, preparing a solution: weigh nickel sulfate, cobalt sulfate, and manganese sulfate crystals according to a molar ratio of 70:15:15, and stir and mix with 40°C deionized water until completely dissolved to obtain a metal salt solution with a total metal ion concentration of 1.5 mol / L, and prepare a 10% sodium hydroxide solution, a 7% ammonia solution, and a 10% sodium carbonate solution.

[0038] Step 2, preparing the bottom liquid: adding deionized water to the reactor, heating to a temperature of 80°C, starting the reactor to stir, and then adding sodium hydroxide solution, ammonia water and sodium carbonate solution to form the reactor bottom liquid, controlling the bottom liquid pH to 11.9, the ammonia concentration to 0.03 mol / L, the reactor stirring linear speed to 8 m / s, and the mass ratio of sodium hydroxide to sodium carbonate in the bottom liquid to be 1:0.9.

[0039] Step 3, open the kettle and let the metal salt solution and sodium hydroxide solution flow to the reactor to react with the bottom liquid for coprecipitation, control the flow rate of the metal salt solution to 4L / h, the flow rate of the sodium hydroxide solution to 1.6L / h, and after the nucleation is stable, open the ammonia valve in the growth stage and flow into the reactor, control the flow rate of the metal salt solution to 4L / h, the flow rate of the sodium hydroxide solution to 1.6L / h, and the flow rate of the ammonia solution to 0.3L / h, and control the pH to 11.7±0.02, the ammonia concentration to 0.2mol / L±0.01mol / L, the temperature to 70°C, and the stirring linear speed to 8m / s during the reaction. During the reaction, when the liquid level of the reaction liquid rises to the upper limit level, turn on the clearing pump to keep the liquid level of the reactor constant.

[0040] Step 4: After the D50 of the material in the reactor is 6 μm, stop the reaction and clear out, and discharge the material.

[0041] Step 5: Wash the material in step 4 with a sodium hydroxide solution having a concentration of 0.5 mol / L for 1 hour, dehydrate it and then wash it with pure water for 1 hour. After dehydration, send it to the drying section, and after drying, send it to the demagnetization and packaging section for treatment to obtain the target precursor.

[0042] The preparation method of the hole structure positive electrode material is: The precursor obtained in the above step 5 is mixed with lithium carbonate in a ratio of total metal ion mole to lithium atomic mole of 1:1.03, and sintered at 800° C. in an oxygen atmosphere for 12 hours to obtain a hole structure positive electrode material.

[0043] Example 3 The preparation method of the porous structure precursor in this embodiment is: Step 1, preparing a solution: weigh nickel sulfate, cobalt sulfate, and manganese sulfate crystals according to a molar ratio of 90:5:5, and stir and mix with 40°C deionized water until completely dissolved to obtain a metal salt solution with a total metal ion concentration of 2.5 mol / L, and prepare a 20% sodium hydroxide solution, a 10% ammonia solution, and a 15% sodium carbonate solution.

[0044] Step 2, preparing the bottom liquid: adding deionized water to the reactor, heating to a temperature of 50°C, starting the reactor to stir, and then adding sodium hydroxide solution, ammonia water and sodium carbonate solution to form the reactor bottom liquid, controlling the pH of the bottom liquid to be 11.8, the ammonia concentration to be 0.05 mol / L, the reactor stirring linear speed to be 8.5 m / s, and the mass ratio of sodium hydroxide to sodium carbonate in the bottom liquid to be 1:1.0.

[0045] Step 3, open the kettle and let the metal salt solution and sodium hydroxide solution flow to the reactor to react with the bottom liquid for coprecipitation, control the flow rate of the metal salt solution to 2L / h, the flow rate of the sodium hydroxide solution to 0.5L / h, and after the nucleation is stable, open the ammonia valve in the growth stage and flow into the reactor, control the flow rate of the metal salt solution to 5L / h, the flow rate of the sodium hydroxide solution to 2L / h, and the flow rate of the ammonia to 0.5L / h, and control the pH to 11.6±0.02, the ammonia concentration to 0.17mol / L±0.01mol / L, the temperature to 70°C, and the stirring linear speed to 8.5m / s during the reaction. During the reaction, when the liquid level of the reaction liquid rises to the upper limit liquid level, turn on the clearing pump to keep the liquid level of the reactor constant.

[0046] Step 4: After the D50 of the material in the reactor is 5.0 μm, stop the reaction and clear out, and discharge the material.

[0047] Step 5: Wash the material in step 4 with a sodium hydroxide solution having a concentration of 0.5 mol / L for 1 hour, dehydrate it and then wash it with pure water for 1 hour. After dehydration, send it to the drying section, and after drying, send it to the demagnetization and packaging section for treatment to obtain the target precursor.

[0048] The preparation method of the hole structure positive electrode material is: The precursor prepared in the above step 5 is mixed with lithium dihydrogen phosphate in a ratio of total metal ion moles to lithium atomic moles of 1:1.02, and sintered at 750° C. in an oxygen atmosphere for 15 hours to obtain a hole structure positive electrode material.

[0049] Comparative Example 1 Compared with Example 1, in this comparative example, no sodium carbonate solution was added to the base liquid, and the ammonia valve was directly opened when the kettle was opened.

[0050] The specific preparation steps of the precursor of this comparative example are as follows: Step 1 is the same as in Example 1.

[0051] Step 2, prepare the bottom liquid: add deionized water to the reactor, heat to 60°C, start the reactor to stir, then add sodium hydroxide solution and ammonia water to form the reactor bottom liquid, control the bottom liquid pH to 12.0, the ammonia concentration to 0.05 mol / L, and the reactor stirring linear speed to 7 m / s.

[0052] Step 3, open the kettle and let the metal salt solution, sodium hydroxide solution and ammonia water flow to the reactor to react with the bottom liquid for coprecipitation, control the flow rate of the metal salt solution to 2L / h, the flow rate of the sodium hydroxide solution to 0.8L / h, and the flow rate of the ammonia water to 0.15L / h, and control the flow rate of the metal salt solution to 2L / h, the flow rate of the sodium hydroxide solution to 0.8L / h, and the flow rate of the ammonia water to 0.15L / h during the growth stage. During the reaction, the pH is controlled to be 11.8±0.02, the ammonia concentration is 0.2mol / L±0.01mol / L, the temperature is 68°C, and the stirring linear speed is 7m / s. During the reaction, when the liquid level of the reaction solution rises to the upper limit liquid level, the clearing pump is turned on to keep the liquid level of the reactor constant.

[0053] Step 4 is the same as in Example 1.

[0054] Step 5 is the same as in Example 1.

[0055] The precursor obtained in step 5 was analyzed by electron microscope. Figure 4 As shown, it can be seen that the obtained precursor does not have a porous structure.

[0056] The preparation method of the positive electrode material is the same as that of Example 1.

[0057] The cross-section electron microscope photo analysis of the obtained positive electrode material showed the following results: Figure 5 As shown, it can be seen that there is no obvious void structure inside the material.

[0058] Comparative Example 2 Compared with Example 1, the mass ratio of sodium hydroxide to sodium carbonate in the base liquid in this comparative example is 1:1.2.

[0059] The specific preparation steps of the precursor of this comparative example are as follows: Step 1 is the same as in Example 1.

[0060] Step 2, preparing the bottom liquid: adding deionized water to the reactor, heating to a temperature of 60°C, starting the reactor to stir, and then adding sodium hydroxide solution, ammonia water and sodium carbonate solution to form the reactor bottom liquid, controlling the pH of the bottom liquid to be 12.0, the ammonia concentration to be 0.05 mol / L, the reactor stirring linear speed to be 7 m / s, and the mass ratio of sodium hydroxide to sodium carbonate in the bottom liquid to be 1:1.2.

[0061] Steps 3 to 5 are the same as those in Example 1.

[0062] The precursor obtained in step 5 was analyzed by electron microscope. Figure 6 As shown, it can be seen that the obtained precursor does not have a porous structure and is relatively dense inside.

[0063] The preparation method of the positive electrode material is the same as that of Example 1.

[0064] The cross-section electron microscope photo analysis of the obtained positive electrode material showed the following results: Figure 7 As shown, it can be seen that there is no void structure inside the material.

[0065] The positive electrode materials prepared in Example 1 and Comparative Example 1 were respectively assembled into button-type lithium-ion batteries, the negative electrodes were all lithium sheets, the electrolyte was 1M LiPF6 / (EC+EMC+DMC), and the diaphragm was a polypropylene microporous diaphragm, and their electrical properties were tested.

[0066] Figure 8 The figure shows the discharge specific capacity of the battery at different rates. It can be seen that the capacity retention rates of the two are basically the same at low rates (0.1C-3C), and the capacity retention rate of the hole structure positive electrode material at high rates is significantly better than that of the button lithium-ion battery prepared in Comparative Example 1. Fig. 9 The figure shows the capacity retention rate of the battery after 50 cycles. It can be seen that the two showed obvious differences from the beginning. The capacity retention rate of the lithium ion battery prepared in Example 1 is significantly better than that in Comparative Example 1.

Claims

1. A method for preparing a porous structure precursor, characterized in that: Follow the steps below to implement it: Step 1, preparing a metal salt solution, a sodium hydroxide solution, an ammonia solution and a sodium carbonate solution; Step 2, preparing a base liquid in a reaction kettle using the sodium hydroxide solution, ammonia water and sodium carbonate solution prepared in step 1; Step 3, the metal salt solution and the sodium hydroxide solution are simultaneously flowed into the reactor to undergo a co-precipitation reaction with the bottom liquid, and after the nucleation is stable, ammonia water is flowed into the reactor to continue the reaction; Step 4, after the particle size of the material in the reactor reaches the qualified particle size, stop the reaction and discharge the material; Step 5, washing the material obtained in step 4 with an alkaline solution and water in turn, and then dehydrating, drying and demagnetizing to obtain a precursor.

2. The method for preparing a porous structure precursor according to claim 1, characterized in that: In step 1, the concentration of the sodium hydroxide solution is 2.5% to 32.5%, the concentration of the ammonia water is 2.5% to 32.5%, and the concentration of the sodium carbonate solution is 2.5% to 35%.

3. The method for preparing a porous structure precursor according to claim 1, characterized in that: In step 1, the metal salt solution is a mixed solution of nickel salt, cobalt salt and manganese salt, wherein the nickel salt is any one of nickel sulfate, nickel fluoride and nickel nitrate; the cobalt salt is any one of cobalt sulfate, cobalt fluoride and cobalt nitrate; the manganese salt is any one of manganese sulfate, manganese fluoride and manganese nitrate; the molar amount of nickel, cobalt and manganese atoms accounts for the total atomic molar amount of nickel, cobalt and manganese respectively. The ratio is x, y and z, wherein 0.6≤x<1.0, 0<y<0.4, 0<y<0.4, x+y+z=1; and the total metal ion concentration in the metal salt solution is 1.5mol / L~2.5mol / L.

4. The method for preparing a porous structure precursor according to claim 1, characterized in that: In step 2, the base liquid is prepared at 50° C. to 80° C., the pH value of the base liquid is 10.5 to 13.0, and the mass ratio of sodium hydroxide to sodium carbonate in the base liquid is 1:0.6-1.

5. The method for preparing a porous structure precursor according to claim 1, characterized in that: During the entire reaction process of step 3, the pH of the reaction solution is controlled at 10.5-13.0, the ammonia concentration is controlled at 0.05 mol / L-0.2 mol / L, the stirring linear velocity is 5.0 m / s-9.0 m / s, the temperature range is 50°C-80°C, the flow rate of the metal salt solution is 1.5 L / h-5 L / h, the flow rate of the sodium hydroxide solution is 0.6 L / h-3 L / h, and the flow rate of the ammonia water is 0.1 L / h-1 L / h.

6. The method for preparing a porous structure precursor according to claim 1, characterized in that: In step 4, the standard of qualified particle size is 2μm<D50<10μm, 0.5<diameter distance<1.0, and the particle size distribution conforms to the normal distribution.

7. The method for preparing a porous structure precursor according to claim 1, characterized in that: In step 5, the alkaline solution is a NaOH solution with a concentration of 0.05 mol / L to 3 mol / L. The ratio of the mass of the material to the volume of the alkaline solution and water during the washing process is material: alkali: water = 1 kg: 5 to 15 L: 5 to 15 L, and the washing time is 0.5 h to 2 h.

8. A method for preparing a hole structure positive electrode material, characterized in that: The method is specifically implemented according to the following steps: mixing the porous structure precursor described in any one of claims 1 to 7 with a lithium salt and then sintering at a high temperature to obtain a hole structure positive electrode material.

9. The method for preparing a positive electrode material with a hole structure according to claim 8, characterized in that: The lithium salt is one of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate. The ratio of the amount of total metal ions in the precursor to the amount of lithium atoms in the lithium salt is 1:1-1.

05. The sintering temperature is 600°C~1000°C and the sintering time is 10h~20h.

Citation Information

Patent Citations

  • Nickel-cobalt-manganese precursor, preparation method of nickel-cobalt-manganese ternary material and lithium ion battery

    CN109616664A

  • Preparation method of hollow lithium ion battery positive electrode material precursor

    CN110921723A

  • Porous precursors, hollow oxides and their applications in cathode materials

    CN114772556B